Brazilian Sign Language corpus: Acre Libras Inventory (Revista de Estudos da Linguagem, 2024)
This paper draws on the theoretical methodological proposal of a Brazilian Sign Language (Libras) corpus to be developed under the scope of the Brazilian Sign Language (Libras) Inventory in the region of Rio Branco municipality, in the State of Acre project. First, we address some issues regarding corpus definitions and characteristics, some aspects of Libras, and documentation of sign languages. Second, we address the methodology used in gathering, transcription and analysis of data from Brazilian Sign Language Inventory focusing on the Region of Rio Branco – Acre, shedding light on the contributions of the gathered data to identification, recognition, valuing, and documentation of the Brazilian Sign Language in use in the State of Acre.